MEASUREMENT OF THE STUDENTS’ ATTITUDE TOWARD A WHOLE-LANGUAGEAPPROACH-BASED LECTURE USING SCORE QUESTIONNAIRES - Nizamuddin Sadiq (LPMPP Universitas Negeri Yogyakarta, 2015)
Abstract: The objective was to investigate students’ attitude toward the implementation of a whole language approach on Reading and Writing for Occupational Purposes Course in the academic year of 2013/2014. The approaches employed were phonological and phoneme awareness, phonic and word study, fluency, vocabulary, comprehension skills and strategies, and writing. The participants were 15 students of the English Language Education Department, Universitas Islam Indonesia. SCORE questionnaire using the Likert’s scale was the instrument. Calculation was to find out score index and categorization by following Riduwan’s (2007) score interpretation criteria. The findings showed that in the simple category, two of ten questions were agreed absolutely (100%), in the clear category, all questions were agreed for 80 %, in the original category, five of thirteen questions reached majority of agreement (100%), in the relevant category, one of five questions was agreed absolutely (100%), and in the enjoyable category, all questions were agreed by 93%. Keywords: a whole language approach, SCORE, score interpretation criteria PENGUKURAN SIKAP MAHASISWA TENTANG PERKULIAHAN BERBASIS A WHOLE LANGUAGE APPROACH DENGAN KUESIONER SCORE Abstrak: Tujuan penelitian ini adalah mengukur sikap mahasiswa terhadap pelaksanaan a whole language approach dalam perkuliahan Reading and Writing for Occupational Purposes Course tahun akademik 2013/2014. Pendekatan yang diterapkan adalah kesadaran fonetik dan fonemik, pelafalan dan kata, kelancaran, kosakata, keterampilan dan strategi membaca komprehensif, dan menulis. Responden penelitian ini adalah 15 maahsiswa Pendidikan Bahasa Inggris Universitas Islam Indonesia. Kuesioner SCOREs dengan skala Likert sebagai instrumen. Penghitungan ditujukan kepada skor indeks dan kategorisasi mengikuti criteria interpretasi skor Riduwan (2007). Hasilnya menunjukkan bahwa pada kategori simple, dua pertanyaan disetujui mutlak (100%), pada kategori clear, semua pertanyaan disetujui sebesar 80%, pada kategori original, lima pertanyaan disetujui mutlak (100%), pada kategori relevant, satu pertanyaan disetujui mutlak (100%), dan pada kategori enjoyable, semua pertanyaan disetujui sebesar 93%. Kata Kunci: pendekatan a whole language, kuesioner SCORE, kriteria interpretasi skor